Quantitative genetic analysis of anxiety trait in bipolar disorder - Contreras Rojas, Javier (2017)
Background:Bipolar disorder type I (BPI) affects approximately 1% of the world population. Although geneticinfluences on bipolar disorder are well established, identification of genes that predispose to the illness has beendifficult. Most genetic studies are based on categorical diagnosis. One strategy to overcome this obstacle is theuse of quantitative endophenotypes, as has been done for other medical disorders.Methods:We studied 619 individuals, 568 participants from 61 extended families and 51 unrelated healthycontrols. The sample was 55% female and had a mean age of 43.25 (SD 13.90; range 18–78).Heritability and genetic correlation of the trait scale from the Anxiety State and Trait Inventory (STAI) wascomputed by using the general linear model (SOLAR package software).Results:we observed that anxiety trait meets the following criteria for an endophenotype of bipolar disorder typeI (BPI): 1) association with BPI (individuals with BPI showed the highest trait score (F = 15.20 [5,24], p =0.009), 2) state-independence confirmed after conducting a test-retest in 321 subjects, 3) co-segregation withinfamilies 4) heritability of 0.70 (SE: 0.060), p = 2.33 × 10–14and 5) genetic correlation with BPI was 0.20, (SE= 0.17, p = 3.12 × 10−5).Limitations:Confounding factors such as comorbid disorders and pharmacological treatment could affect theclinical relationship between BPI and anxiety trait. Further research is needed to evaluate if anxiety traits arespecially related to BPI in comparison with other traits such as anger, attention or response inhibition deficit,pathological impulsivity or low self-directedness.Conclusions:Anxiety trait is a heritable phenotype that follows a normal distribution when measured not only insubjects with BPI but also in unrelated healthy controls. It could be used as an endophenotype in BPI for theidentification of genomic regions with susceptibility genes for this disorder